Porous PEDOT:PSS Particles and their Application as Tunable Cell Culture Substrate. Issue 1 (27th September 2021) - Rauer, Sebastian Bernhard; Bell, Daniel Josef; Jain, Puja; Rahimi, Khosrow; Felder, Daniel; Linkhorst, John; Wessling, Matthias
Abstract: Due to its biocompatibility, electrical conductivity, and tissue‐like elasticity, poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) constitutes a highly promising material regarding the fabrication of smart cell culture substrates. However, until now, high‐throughput synthesis of pure PEDOT:PSS geometries was restricted to flat sheets and fibers. In this publication, the first microfluidic process for the synthesis of spherical, highly porous, pure PEDOT:PSS particles of adjustable material properties is presented. The particles are synthesized by the generation of PEDOT:PSS emulsion droplets within a 1‐octanol continuous phase and their subsequent coagulation and partial crystallization in an isopropanol (IPA)/sulfuric acid (SA) bath. The process allows to tailor central particle characteristics such as crystallinity, particle diameter, pore size as well as electrochemical and mechanical properties by simply adjusting the IPA:SA ratio during droplet coagulation. To demonstrate the applicability of PEDOT:PSS particles as potential cell culture substrate, cultivations of L929 mouse fibroblast cells and MRC‐5 human fibroblast cells are conducted. Both cell lines present exponential growth on PEDOT:PSS particles and reach confluency with cell viabilities above 95 vol.% on culture day 9. Single cell analysis could moreover reveal that mechanotransduction and cell infiltration can be controlled by the adjustment of particle crystallinity. Abstract : This publication shows a microfluidic approach for the synthesis of spherical, porous PEDOT:PSS particles with adjustable material properties. The particles are synthesized by generation of PEDOT:PSS dispersion droplets within a 1‐octanol continuous phase and their subsequent coagulation. The particles are successfully applied as substrate for mammalian cell culture and the influence of tunable material properties on cell behavior was investigated.